Economic Growth, Educational Attainment, And Open Unemployment As Determinants Of Poverty: Evidence From South Sulawesi - Muh. Asra’ul Khairi Susanto; Sri Astuty; Muhammad Syafri; Shadry Andriani; Basri Bado (Economics and Business Journal (ECBIS), 2026)
Poverty remains one of the major development challenges in South Sulawesi, particularly in regencies with relatively high poverty rates. This study aims to examine the effects of Gross Regional Domestic Product (GRDP) growth, educational attainment, and the open unemployment rate on poverty across nine regencies in South Sulawesi during the 2016–2025 period. This research employed a quantitative approach using panel data obtained from the Statistics Indonesia. The research sample consisted of nine regencies that consistently recorded high poverty rates, namely Selayar Islands Regency, Jeneponto Regency, Pangkajene and Islands Regency, Bone Regency, Enrekang Regency, Luwu Regency, Tana Toraja Regency, North Luwu Regency, and North Toraja Regency. The analytical method applied was panel data regression using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with the optimal model selected through the Chow test and Hausman test. The findings reveal that GRDP growth has a negative effect on poverty, educational attainment has a negative and statistically significant effect on poverty, whereas the open unemployment rate has a positive effect on poverty. Simultaneously, GRDP growth, educational attainment, and the open unemployment rate significantly influence poverty in South Sulawesi. These findings suggest that poverty alleviation policies should prioritize equitable economic growth, improvements in educational quality, and the expansion of productive employment opportunities.